FAKTOR-FAKTOR YANG MEMPENGARUHI STRES KERJA ANGGOTA BAWASLU KABUPATEN SUMEDANG DALAM MENGAWAL TAHAPAN PEMILU - Sulastri, Lalas; Yasinta, Della Cahyani; Indrayanti, Wiwin Novita; Khoerudin, Abdul Fatah (JRPA - Journal of Regional Public Administration, 2023)
The purpose of this research is to identify the elements that influence the work stress of Sumedang Regency Bawaslu members monitoring the election stages. Qualitative research was employed. Purposive sampling was used, with commissioners, staff, and technical implementers included. Data reduction, data presentation, data presentation, conclusion drawing/verification, and triangulation are all data collection procedures. The study's findings indicate that, from an environmental standpoint, it has little influence because, as implementing agencies, the RI Bawaslu and the Provincial Bawaslu have foreseen the timetable of operations and the budget. From an organizational standpoint, it is highly influential in terms of the workload and tasks that each member has, and it's just that each member already has work resilience due to previous election experience. From a personal standpoint, influence is a sign of individual characteristics, as Bawaslu interacts with a variety of groups, including political organizations, contestants, and the general public. The research findings are expected to strengthen monitoring on social media, facilities and infrastructure, and office layout so that members are more comfortable at work and there are activities that can sustain job resilience